Accuracy of Core Biopsy without Image Guidance in the Tissue Diagnosis of Breast Lump - Hoq, Md Rashidul; Khan, Shahidul Islam; Sayeed, Ahmed (IAHS Medical Journal, 2022)
Background: A breast lump is a localized swelling, protuberance, bulge or lump in the breast that feels different from the breast tissue around it or the breast tissue in the same area of the other breast. The aim of this study is to assess the accrurcy/efficacy of the free hand percutatnous core biopsy without image guidance for the palpable radiologically suspicious breast lump. Materials and methods: This is a retrospective cross sectional study based on reviewing the histopathological reports (59) of all patients of suspicious breast lump in a single center (By single surgeon, single pathologist). Study period was from July 2019 to June 2020. Results: The absolute sensitivity of free hand core biopsy for diagnosis of Carmona palpable lesion was 98%and was statically significant (p<.00) and t=43.51. 2% found Carcinoma and other breast diseases. Conclusion: So considering the accuracy of tissue diagnosis of palpable suspicious breast lump is so high that image guidance is unnecessary. IAHS Medical Journal Vol 4(2), December 2021; 28-31